2014
DOI: 10.1161/atvbaha.113.302598
|View full text |Cite
|
Sign up to set email alerts
|

Functionality of Endothelial Cells and Pericytes From Human Pluripotent Stem Cells Demonstrated in Cultured Vascular Plexus and Zebrafish Xenografts

Abstract: Objective-Endothelial cells (ECs), pericytes, and vascular smooth muscle cells (vSMCs)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
187
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 179 publications
(196 citation statements)
references
References 48 publications
7
187
2
Order By: Relevance
“…S3 A and B). EFNB2 and EPHB4 were the first identified and most widely used markers for AECs and VECs, respectively (6)(7)(8)(9)(10)(11)(12)(13)17). Specific targeting of the EFNB2 and EPHB4 locus was confirmed by junction PCR and Southern blot analysis (SI Appendix, Evaluation of Candidate Factors for Arteriovenous Specification.…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…S3 A and B). EFNB2 and EPHB4 were the first identified and most widely used markers for AECs and VECs, respectively (6)(7)(8)(9)(10)(11)(12)(13)17). Specific targeting of the EFNB2 and EPHB4 locus was confirmed by junction PCR and Southern blot analysis (SI Appendix, Evaluation of Candidate Factors for Arteriovenous Specification.…”
Section: Significancementioning
confidence: 99%
“…Previous studies have shown progress in AEC differentiation (6)(7)(8)(9)(10)(11)(12)(13)(14), but the arterial-specific functions in vitro and the protection of ischemic tissue in vivo have not been well demonstrated in the resulting cells. Here, we use single-cell RNA sequencing (RNA-seq) of early mouse AECs and a CRISPR/Cas9-generated EFNB2-tdTomato/EPHB4-EGFP dual reporter human embryonic stem cell line to develop a protocol for differentiating human pluripotent stem cells into AECs using fully defined culture conditions.…”
mentioning
confidence: 99%
“…with ECs in vitro demonstrate endothelial sprouting (Orlova et al, 2014a) (co-culture study). This has been demonstrated using pericytes derived from hiPSC and adventitial sorted cells from human saphenous vein digests (Campagnolo et al, 2010;Orlova et al, 2014a).…”
Section: Vascularisationmentioning
confidence: 99%
“…This has been demonstrated using pericytes derived from hiPSC and adventitial sorted cells from human saphenous vein digests (Campagnolo et al, 2010;Orlova et al, 2014a). Recapitulation of these phenomena in in vivo implantations would be highly advantageous.…”
Section: Vascularisationmentioning
confidence: 99%
See 1 more Smart Citation